Art after money, money after art : creative strategies against financialization - Haiven, Max, 1981- (Pluto Press ;, 2018)
"We imagine that art and money are old enemies, but this myth actually reproduces a violent system of global capitalism and prevents us from imagining and building alternatives. From the chaos unleashed by the 'imaginary' money in financial markets to the new forms of exploitation enabled by the 'creative economy' to the way art has become the plaything of the world's plutocrats, our era of financialization demands that we question our romantic assumptions about art and money. By exploring the way contemporary artists engage with cash, debt, and credit, Haiven identifies and assesses a range of creative strategies for mocking, sabotaging, exiting, decrypting, and hacking capitalism today. Written for artists, activists, and scholars, this book makes an urgent call to unleash the power of the radical imagination by any media necessary."--